2023
DOI: 10.2991/978-94-6463-042-8_150
|View full text |Cite
|
Sign up to set email alerts
|

Research on Digital Marketing Strategy of Cross-border Retail Platform Based on STV Model: Taking Amazon as an Example

Abstract: Given that the Internet has promoted the overall transformation of international trade, the global marketing strategy of cross-border retail platform enterprises must be adjusted in accordance with the development of emerging Internet technologies and the digital business environment. The article aims to construct a new digital marketing model for crossborder retail platform enterprises based on STV marketing theory, which emphasizes on the target marketing, crossover marketing and forming platform alliances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zheng Linling studies the cross-cultural communication of Chinese traditional culture by taking the Genshin Impact plot PV The Divine Damsel of Devastation as an example [4]. In addition, Zhang Dandan studied the IP cross-border marketing strategy of CRYPTON and put forward relevant suggestions for continuous optimization of the IP development system [5]. Pan Meixiu and Yang Min suggested that traditional time-honored brands should be empowered again by IP-based cross-border marketing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng Linling studies the cross-cultural communication of Chinese traditional culture by taking the Genshin Impact plot PV The Divine Damsel of Devastation as an example [4]. In addition, Zhang Dandan studied the IP cross-border marketing strategy of CRYPTON and put forward relevant suggestions for continuous optimization of the IP development system [5]. Pan Meixiu and Yang Min suggested that traditional time-honored brands should be empowered again by IP-based cross-border marketing [6].…”
Section: Introductionmentioning
confidence: 99%